Peran Media Sosial TikTok terhadap Minat Pemakaian Basic Skincare pada Mahasiswa Fakultas Ilmu Keolahragaan Universitas Negeri Semarang - Nisrina Adzra Nabihah Heryanto; Ifa Nurhayati; Ade Novi Nurul Ihsani; Anik Maghfiroh (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
TikTok social media is one of the digital platforms that is widely used by students and has the potential to influence consumption preferences, including the use of basic skincare products. This study aims to find out the role of TikTok content in helping students of the Faculty of Sports Sciences, Semarang State University, in choosing basic skincare products. The research uses a descriptive quantitative approach with purposive sampling techniques. Data was collected through a questionnaire on 18 students of the Elementary School Physical Education Study Program class of 2024. The results showed that 91.5% of respondents stated that TikTok content played a role in increasing interest in using basic skincare, while 8.5% of respondents stated that this interest was influenced by other factors. These findings show that TikTok has a strong role in shaping students' interest in the use of basic skincare products, although the results of the study are still limited to the number and characteristics of respondents.